Cervical vestibular evoked myogenic potentials in 3-month-old infants: Comparative characteristics and feasibility for infant vestibular screening - Shen, Jiali; Wang, Lu; Ma, Xiaobao; Chen, Zichen; Chen, Jianyong; Wang, Xueyan; He, Kuan; Wang, Wei; Sun, Jin; Zhang, Qin; Shen, Min; Chen, Xiangping; et al. (Frontiers in Neurology, 2022)
Objective We compared the characteristics of air-conducted sound cervical vestibular evoked myogenic potential (ACS-cVEMP) and bone-conducted vibration cVEMP (BCV-cVEMP) among 3-month-old infants with normal hearing and sensorineural hearing loss (SNHL), and healthy adults to explore the feasibility and optimal strategies for infant vestibular screening. Methods 29 infants (58 ears) were divided into two groups according to hearing (group I: normal hearing ears; group II: SNHL ears), 20 healthy adults were defined as group III. The results of response rate, P13 and N23 latency, P13-N23 interval, amplitudes, and corrected interaural asymmetry ratio (IAR) were recorded and compared among three groups. Results The response rates of ACS-cVEMP in three groups were 88.89, 62.00, 100%, respectively. The P13 and N23 latencies, and P13-N23 interval did not differ significantly between group I and II (p = 0.866, p = 0.190, p = 0.252). A significant difference was found between group I and III (p = 0.016, p < 0.001, p < 0.001). No significant difference was observed in raw or corrected amplitude between group I and II (p = 0.741, p = 0.525), while raw and corrected amplitudes in group III were significantly larger than group I (p < 0.001, p < 0.001). For BCV-cVEMP, the response rates in three groups were 100, 86.36, 100%, respectively, No significant difference existed in the P13 and N23 latency, or P13-N23 interval between group I and II (p = 0.665, p = 0.925, p = 0.806), however, P13 and N23 latencies were significantly longer in group III than group I (p < 0.001, p = 0.018), but not in P13-N23 interval (p = 0.110). There was no significant difference in raw or corrected amplitude between group I and II (p = 0.771, p = 0.155) or in raw amplitude between group I and III (p = 0.093), however, a significant difference existed in corrected amplitude between group I and III (p < 0.001). Conclusions Compared with adults, 3-month-old infants with normal hearing presented with equivalent response rates, shorter P13 and N23 latencies, smaller corrected amplitudes, and a wider IAR range for both ACS and BCV-cVEMP. SNHL infants had equivalent response rates of BCV-cVEMP, lower response rates of ACS-cVEMP than normal hearing infants. When responses were present, characteristics of ACS and BCV-cVEMP in SNHL infants were similar with normal hearing infants. ACS combined with BCV-cVEMP are recommended to improve the accuracy of vestibular screening.